IMMEDIATE OUTCOME AND SAFETY OF REDO PTMC - Ali, Khurshid; Ahmad, Sajjad; Samin, Ariz; Yasmin, Samra; Ahsan, Zameer Ul; Abbasi, Muhammad Amad; Bibi, Hajra; Tariq, Filza; Kamran, Javeria; Samore, Naseer Ahmed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess and compare the immediate procedural success of percutaneous transvenous mitral commissurotomy and safety in those patients who had undergone a prior percutaneous transvenous mitral commissurotomy. Study Design: Single-center, retrospective study. Place and Duration of Study: Angiography department, Punjab Institute of Cardiology, Lahore, from Jan 2019 to Jun 2020. Methodology: Medical records of all those patients who underwent redo percutaneous transvenous mitral commissurotomy (PTMC) were included. Mitral valve area (MVA), left atrial (LA) pressure, pulmonary artery systolic pressure (PASP), and mitral regurgitation (MR) were compared before and after procedure. Results: There were 39 patients 22 (56%) males and 17 (44%) females with a mean age 37.15 ± 2.63 enrolled age range between 25-45 years. The difference in left atrial pressure, mitral valve area and pulmonary artery systolic pressure between pre and post redo percutaneous transvenous mitral commissurotomy was statistically significant (p-value=0.001). Conclusion: Redo percutaneous transvenous mitral commissurotomy is a feasible and safe procedure in significant mitral restenosis. The results are optimal with acceptable morbidity and mortality.